THE EFFECT OF CUSTOMER VALUE DIMENSIONS TO DESCRIBE CUSTOMER SATISFACTION AND BEHAVIORAL INTENTION OF SHARIA BANKS IN INDONESIA - Budiyono, Iwan; Murtiasri, Eka (MALIA: Journal of Islamic Banking and Finance, 2018)
This study examines the relationship of customer value (CV) dimension added with the spirituality dimension to the satisfaction (KPN) and its impact on the Behavior Intention (BI) of the customers in Sharia Bank savings in Indonesia. Using a customer value approach that consists of: functional, social, emotional and spiritual. The sample consists of 41 people from the Sharia Bank savings of sharia bank population in Indonesia. Samples were collected through the spread of an online questionnaire. The method used is Multiple Linear Regression using SPSS 23 program. The result shows that there is positive influence of customer dimension to customer satisfaction, positive influence of customer value dimension toward behavioral intention and positive influence between customer satisfaction toward behavioral intention.